Penguatan Identitas Komunitas Waria Dan Gay (Wargas) Melalui Kegiatan Sosial Di Masyarakat Kota Singaraja - Darmayanti, Kadek Nanda Weda; Sendratari, Luh Putu; Idris, Muhammad (CV. Publikasi Indonesia, 2025)
This study aims to find out the factors behind the Wargas community strengthening their identity; forms of social activities carried out by the Wargas community; and to find out the aspects of strengthening the identity of the Wargas community that can be used as a learning resource. This study uses a type of descriptive research with a qualitative method. The data collection methods applied are interviews, observations, and document studies. Primary and secondary data are used as data sources. Triangulation of sources and methods is used to check the validity of the data. The interactive analysis technique of Miles and Huberman is used as a data analysis technique. The findings of this study are in the form of factors that are behind the community of Wargas to strengthen identity, namely the context between groups, in-group attractiveness, personal beliefs, and depersonalization. The social activities carried out by the Wargas community are HIV/AIDS prevention activities, caring activities for others, special English learning places, and environmental care activities. The source of teaching materials used is PowerPoint, a problem-based learning method related to gender deviation material. This research helps increase social understanding and increase inclusivity and tolerance.